The Role of Culture in Behavioral Aspects of Green Accounting to Promote Renewable Energy Business - I Gusti Putu Eka Rustiana Dewi; Ni Made Sintya Surya Dewi (Jurnal Minfo Polgan, 2023)
The cultural element has had a significant impact on implementation of green accounting and the growth of the green business movement. Businesses need to be aware of how culture affects them and should get ready for the difficulties these cultural components will encounter. This is due to the diverse cultures found in each location and nation. Therefore, culture is one of the aspects that will impact behavior and the sustainability of the firm when running a business and applying green accounting in business. The research method used is descriptive qualitative method with literature review research that emphasizes in depth understanding of the content of behavioral aspects in green accounting implementation. Qualitative research method explores data using observation methods and library research, this research involves looking through books, documents, scientific publications, research journals, and other materials connected to the research title. The study is aim to find the role of culture affect behavior aspects in order to implement of green accounting to boost renewable energy business in Indonesia. Technology and investment are not only two factors contributing to the slow growth of renewable energy; human behavior that affected by social culture should also be considered in order to shift behaviors to promote activities.